Inequality, life expectancy, and the intragenerational redistribution puzzle: Some experimental evidence - Tim Krieger; Christine Meemann; Stefan Traub (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2022)
In most OECD countries, pension reform policy has decreased the level of intragenerational redistribution over the last three decades, that is, redistribution among members of the same generation with high and low pension entitlements. This trend has occurred despite heterogeneity in life expectancy linked to socioeconomic status having a regressive impact on outcomes. This paper contributes to solving this puzzle by means of a controlled laboratory experiment. We study the causal relationship between inequality of entitlements, mortality risk, and the size of redistribution in a stylized social security system. We find that mortality risk, when negatively correlated with entitlements, significantly lowers subjects' willingness to redistribute payoffs from high-entitlement to low-entitlement subjects. We explain this finding with efficiency preferences and an alienation effect. The alienation effect is the tendency to attach a lower social weight to the short-lived poor.
Keywords: D63; D81; H55; I14; 330; Inequality; Life Expectancy; Risk; Redistribution; Pension Reform; Efficiency Preferences; Alienation Effect; Experiment